Alma Mater Studiorum. On the origin and the beginnings of universities - Maciejewski, Marek (The Opole Studies in Administration and Law, 2017)
The origin of universities reaches the period of Ancient Greece when philosophy (sophists, Socrates, Plato, Aristotle, stoics and others) – the “Queen of sciences”, and the first institutions of higher education (among others, Plato’s Academy, Cassiodorus’ Vivarium, gymnasia) came into existence. Even before the new era, schools having the nature of universities existed also beyond European borders, including those in China and India. In the early Middle Ages, those types of schools functioned in Northern Africa and in the Near East (Baghdad, Cairo, Constantinople, cities of Southern Spain). The first university in the full meaning of the word was founded at the end of the 11th century in Bologna. It was based on a two-tiered education cycle. Following its creation, soon new universities – at first – in Italy, then (in the 12th and 13th century) in other European cities – were established. The author of the article describes their modes of operation, the methods of conducting research and organizing students’ education, the existing student traditions and customs. From the very beginning of the universities’ existence the study of law was part of their curricula, based primarily on the teaching of Roman law and – with time – the canon law. The rise of universities can be dated from the end of the Middle Ages and the beginning of modernity. In the 17th and 18th century they underwent a crisis which was successfully overcome at the end of the 19th century and throughout the following one.